Dynamics of Global Terrorism - Kumar, Ashok (New Delhi, 2014)
This book on Dynamics of Global Terrorism covers the various aspects of the global terrorism. The problem of terrorism is not a recent one but is as old as human civilization. It deals with the problem of terrorism which is a complex problem having international dimensions and is affecting the international relations of the countries in the recent times. Terrorism is considered as a method whereby an organized groups seek to achieve its vowed in chiefly through the systematic use of violence. The book discusses the gravity of the problem of terrorism both at National as well as International level, profile of 'terrorists' and terrorist's organizations, weapons used by terrorists, designated and non-designated terrorist organizations, legal principles against terrorism. The book also discusses the concept of terrorism, definition of terrorism, causes and effects of terrorism, kinds and methodology of terrorism, global scenario of terrorism and efforts to combat, terrorism in India specially the issue of Kashmir and North East states. Insurgency and naxalism in some parts of the country, statutory safeguards for prevention, control and abatement of terrorism, terrorism vis a vis human rights violation, role of judiciary in combating terrorism and for the prevention, control and abatement of terrorism menace. Some suggestions are also offered:- such as launching of a national campaign for eradication of terrorism, formulation of a special national law on terrorism, organization of comprehensive and integrated system of security, national awakening about terrorism and terrorists, formulation of citizen security bill, introduction of national identity cards for citizens, implementation of national e-governance grid, accelerated development of terrorist affected zones, employment to the youth in terrorist affected areas, mobilization of public in the fight against terrorism, establishment of peace missions, posting of honest and brave officers in terrorists areas and sufficient co-ordination between and intelligence agencies.
Keywords: "Terrorism, Global terrorism"